Analysis of Risk Factors for Amputation in 822 Cases with Acute Arterial Emboli. (19th April 2012) - Dag, Ozgur; Kaygın, Mehmet Ali; Erkut, Bilgehan
Abstract : Background . We retrospectively examined the records of 822 patients who underwent a total of 901 operations for acute peripheral arterial occlusion of the upper or lower extremities between 1999 and 2009. We analyzed the effects of atherosclerotic structure, the time of admission to hospital, and re-embolectomies on amputation in the early postoperative period. Methods . There were 466 (56.7%) men and 356 (43.3%) women. The time of admission to hospital was in the range of 58 hours. There were lower extremity emboli in 683 (83%). Bypass procedures were done in 27 (3.3%) patients. Fasciotomy, patchplasty, and endarterectomy were made in 19 (2.3%), 9 (1.1%), and 7 (0.8%) patients, respectively. Results . Early revision (re-embolectomy) was performed in 77 (9.3%) patients. Amputation was performed in 112 (13.6%) patients. Delay after six hours from the onset of complaints and re-embolectomies increased the risk of amputation and rates. Conclusion . If the embolectomy, which is a rapid and easy technique for treatment of acute arterial emboli, is performed by experienced surgeons without delay, the complications associated with the emboli may be prevented. Otherwise, delayed operation and repeated re-embolizations in acute arterial play important roles in morbidity.